Smart Door Locking System for Children Using HC-SR04 and IoT Technology - Melinda Melinda; Yunidar Yunidar; Syaidatul Khairia; Rizka Miftahujjannah; Gopal Sakarkar; Nurlida Basir (Universitas Andalas, 2026)
Indexed by Scopus